The "Spaghetti Bowl": A case study on processing rules of origin and rules of cumulation - Ulrich Schüle; Tatiana Kleisinger (University of Applied Sciences Mainz, 2016)
The "Spaghetti Bowl" (or "Noodle Bowl") phenomenon describes the trade-distorting effects caused by the multitude of Regional Trade Agreements (RTAs) signed in the last three decades. As RTAs allow for a different treatment of imports from different countries, rules defining a product's country of origin play a crucial role in these agreements. Therefore, RTAs apply so-called Rules of Origin (RoO) and Rules of Cumulation (RoC) with the latter allowing companies to use input material from other contracting countries without jeopardising the product's originating status. With many RTAs having been signed in the last decades, a multitude of contradicting RoO and RoC are in force. They contribute to trade diversion and a loss of economic welfare in both, the suppliers' and the importing country. A vast number of studies analysed and discussed these trade diverting effects - with an overwhelming majority of them focusing on macroeconomic and political aspects. There is, however, little research on how companies deal with the administrative burden the application of the many partly ambiguous, partly contradicting RoO and RoC imposes on them. A detailed analysis of how a company organises the work flow and secures a proper RoO documentation has not yet been published. In this paper, we describe and analyse the organisation of the "origin management" of a large supplier to the car-assembling industry. The case study adds value to the existing knowledge by providing an insight into a company's documentation of the products' origin, in particular with regard to the so-called "Bill of Materials". Issues of data management are discussed. Thus, the paper adds the in-company view to the preponderantly macroeconomic literature.
Keywords: 650; Spaghetti Bowl; Rules of Origin; Rules of Cumulation; Trade Diversion; Material Documentation; Origin Management